Characterization of Rubber Seed (Hevea Brasiliensis) as Raw Material for The Production of Biofuel - Ayuni Lestari; Muhammad Yerizam; Abu Hasan (Journal of Applied Agricultural Science and Technology, 2023)
Rubber seeds from the Musi Rawas region in South Sumatra have great potential for rubber seed plantations. However, their utilization has not been maximized and they are often treated as plantation waste. This research aims to obtain the characteristics of rubber seeds as raw materials for biofuel production, so that the rubber seeds from the South Sumatra region can be utilized by the community and not just considered as plantation waste. In the first treatment, the rubber seeds are crushed to obtain the seed coat and the kernel. The crushed rubber seed shells are finely ground and sieved, while the kernel is pressed to extract vegetable oil using a pressing tool. The test methods used to determine the characteristics of the rubber seed shells include proximate analysis and calorific value, while GC-MS analysis is employed for the rubber seed oil. The proximate analysis of the rubber seed shell (RSS) yielded the following results: moisture content of 15.97 wt%, volatile matter of 47.43 wt%, fixed carbon of 32.45 wt%, and ash content of 4.15 wt%. The calorific value of the rubber seed shell was found to be 3312.8694 calories per gram. For the GC-MS yield of the rubber seed oil, the composition is as follows: palmitic acid 7.32%, linoleic acid 34.69%, oleic acid 45.35%, and pentadecanoic acid 8.86%. Based on the obtained results, rubber seeds show promising potential as raw materials for biofuel production through the pyrolysis process.